Juvenile Justice for the Best Interest of the Children in Bangladesh: A Legal Analysis - Ferdousi, Nahid (2013)
This paper attempts to analyze the legal mechanisms of juvenile justice in Bangladesh whether it complies with international standards and to what extent the national legislation protect children’s wellbeing as a whole. Since independence of Bangladesh in 1971, the first expression of concern about the protection of children came through the Children Act 1974, the unique principle for children in relating to trial, custody, protection, punishment, treatment and reformation. Although Bangladesh entered the new phase of juvenile justice system by the Act, which is 38 years old does not reflect many principles of the Convention on the Rights of the Child (CRC) 1989. In 1990, after signing the CRC, the law and policy has not substantially been changed which ensures that juveniles are separated and treated differently from adults and to protect their best interest during all kinds of legal processes. In practice, often the Act is not being implemented and as a result children receive the same treatment as adults. Consequently, children suffer adversely from existing laws and practices. In this context, recently, the Children Act 2013 has enacted on the basis of the CRC that Bangladesh ratified 23 years ago; the second phase of the juvenile justice system would be started with the new Act, it is not implemented yet. Against this backdrop, the study assesses both legal development and practices of the juvenile justice system as well as for the best interest of the children in Bangladesh. Keywords: Juvenile justice, children wellbeing, legal context, international standard, child-friendly justic